Unmet medical needs in glioblastoma management and optimal sequencing of the emerging treatment options - Schnell, Oliver; Tonn, Jörg Christian (European journal of Clinical and Medical Oncology, 2010)
The standard treatment for patients with newly-diagnosed glioblastoma multiforme includes microsurgical tumor resection, external beam radiation in combination with temozolomide (TMZ) chemotherapy, and then adjuvant chemotherapy with TMZ alone. In addition, there are new drugs targeting different key players in tumorigenesis and angiogenesis in malignant gliomas that are currently being tested in clinical trials. Thus, more sophisticated molecular and genetic profiling will be necessary to determine which patients are most likely to benefit from the specific treatment options. In cases of unavoidable tumor recurrence, no clear standard of therapy exists, and there is no expert consensus on how to treat these patients. Re-resection, re-radiation, or changes in chemotherapeutic schedule or drug are general options, but each has to be considered on a case-by-case basis. In addition, institutions often have some mostly experimental local or systemic approaches that are considered in recurrent glioblastomas. This has led to growing uncertainty as to how to treat patients with glioblastomas and recurrent disease and when to use which therapeutic option. Decision-making also depends on the time point of therapy onset, and therefore also the correct detection of real tumor progression. Magnetic resonance imaging (MRI) has been demonstrated to have diagnostic limitations in cases of "pseudoprogression" after multimodal therapy and in patients treated with antiangiogenic drugs. Thus, new imaging techniques such as MR spectroscopy, MR FLAIR sequences, ADC maps, and nuclear medicine imaging with O-(2-[18F]fluoroethyl)-L-tyrosine positron emission tomography (FET-PET) or other tracers will be of almost as much importance in the treatment of glioblastoma as the different tumor therapies in due time.
CRIS-Team Scopus Importer:2023-09-13
Keywords: Glioblastoma multiforme (GBM); Microsurgical tumor resection; Molecular markers; Pseudoprogression; Radiochemotherapy with temozolomide (TMZ); Stereotactical serial biopsy; Targeted therapy